Discurso científico e ideologia na revista do Estado Novo, Portugal colonial - Duarte, Isabel Margarida (2018)
Based on a discursive-pragmatic theoretical framework, we define as object of analysis the construction of scientific discourse in the Magazine Portugal Colonial, published during Estado Novo, in order to determine the discursive modes of construction of science in relation to the ideology of the Portuguese Estado Novo regime. Portugal Colonial is a monthly magazine of propaganda, published from March of 1931 to February of 1937. Unlike the stereotype of the scientist and his work, both confined to an ivory tower, it is not possible to understand science outside its socio-historical context. In other words, it is not possible to think of science as breaking away from ideology. This is also the case: textual elements point to a strong association between science and ideology in the articles analyzed.